Diagnosing Pulsatile Tinnitus: A Review of 251 Patients. Issue 1 (January 2022) - Lynch, Patrick; Mitton, Tanner; Killeen, Daniel E.; Kutz, Joe Walter; Newcomer, Mark
Abstract : Objective: To analyze the underlying etiologies, presenting characteristics, and diagnostic workup of patients with pulsatile tinnitus (PT). Study Design: Retrospective review. Setting: Tertiary referral center. Patients: All patients who received a diagnostic workup for PT from January 01, 2015 and May 31, 2020. Main Outcome Measure: Diagnostic rate of imaging studies. Results: Among 251 patients with PT, the most common etiologies included neoplasms (16%), arteriopathies (14%), venopathies (8.5%), middle/inner ear pathology (9.0%), or idiopathic (50%). Patients with identifiable etiologies of PT more often had hypertension, obesity, vision changes, ipsilateral asymmetric hearing loss, or an abnormal otologic examination. Only 18.5% of patients without those characteristics had an identifiable etiology of PT. The most commonly ordered diagnostic studies were magnetic resonance imaging with contrast (n = 146), MR angiography (MRA) (n = 105), CT angiography (CTA) (n = 84), computed tomography (CT) without contrast (n = 76), and MR Venogram (MRV) (n = 62). Magnetic resonance imaging with contrast and CT without contrast preferentially identified patients with nonvascular etiologies of PT, while MRA and CTA identified patients with vascular etiologies of PT. MRV did not demonstrate high diagnostic rate for either type of PT. No difference in diagnostic rate was found between MR-based or CT-based imaging. Conclusions: Patients who lack a history of hypertension, obesity, vision changes, ipsilateral asymmetric hearing loss, or an abnormal otologic examination are less likely to have an identifiable cause for PT. In cases where a specific etiology was identified, MR-based imaging (MRI with contrast and MRA) or CT-based imaging (CT without contrast and CTA) were equally efficacious in identifying that etiology. MR-based imaging is preferred for neoplasms, while CT-based imaging is preferred for semicircular canal dehiscence. Abstract : Supplemental Digital Content is available in the text